EFEKTIVITAS KOMUNIKASI NEGOSIASI DALAM BISNIS - Dwi Utami, Faiqotul Isma (UIN Mataram, 2017)
The need for communication in today’s business competition is constantly changing. The process of negotiation becomes an important thing in supporting the progress of a business. Negotiations are used to bridge different interests, between producers and consumers. A negotiator must be able to persuade the other person so that they can follow the negotiator’s will without them knowing it. This paper explains how a business can communicate more effectively so that he can become a good negotiator.